LIFE EVALUATION OF THE CASTING REPAIR PART AT THE END OF THE WORK ROLL NECK OF A FOUR-HIGH ROLLING MILL - QU HaiXia; QIN XiaoFeng (Jixie qiangdu)
As the core component of strip mills,roll consumption has an essential influence on the production cost.With the increasing demand for cost reduction and efficiency increase caused by the intensifying competition of iron and steel enterprises,the recycling of roll re-manufacturing has been gradually promoted.It is one of the main ways to transform the largesize roll of the large rolling mill to a small rolling mill after its work layer consumption.For rolls with local size,especially those with insufficient shoulder size,casting lengthening is usually adopted to meet the needs of further use.The service life of the roll after casting joint repair and re-manufacturing becomes the key to ensuring safe production.Because of the above problems,the fatigue performance test was carried out on the roll casting part sample.At the same time,the torsional fatigue model was used to predict the life of the roll neck after the repair of the work roll based on proving the calculation accuracy and combining it with the load spectrum established based on the field production data.The expected service life met the performance requirements of the repaired roll on the site.It can provide theoretical support for establishing an on-site roll safety maintenance system.